Investigating the Individual Performances of Coupled Superconducting Transmon Qubits - Halima Giovanna Ahmad; Caleb Jordan; Roald van den Boogaart; Daan Waardenburg; Christos Zachariadis; Pasquale Mastrovito; Asen Lyubenov Georgiev; Domenico Montemurro; Giovanni Piero Pepe; Marten Arthers; Alessandro Bruno; Francesco Tafuri; et al. (Condensed Matter, 2023)
The strong requirement for high-performing quantum computing led to intensive research on novel quantum platforms in the last decades. The circuital nature of Josephson-based quantum superconducting systems powerfully supports massive circuital freedom, which allowed for the implementation of a wide range of qubit designs, and an easy interface with the quantum processing unit. However, this unavoidably introduces a coupling with the environment, and thus to extra decoherence sources. Moreover, at the time of writing, control and readout protocols mainly use analogue microwave electronics, which limit the otherwise reasonable scalability in superconducting quantum circuits. Within the future perspective to improve scalability by integrating novel control energy-efficient superconducting electronics at the quantum stage in a multi-chip module, we report on an all-microwave characterization of a planar two-transmon qubits device, which involves state-of-the-art control pulses optimization. We demonstrate that the single-qubit average gate fidelity is mainly limited by the gate pulse duration and the quality of the optimization, and thus does not preclude the integration in novel hybrid quantum-classical superconducting devices.